Valence‐band electronic structure evolution of graphene oxide upon thermal annealing for optoelectronics. Issue 9 (4th April 2016) - Yamaguchi, Hisato; Ogawa, Shuichi; Watanabe, Daiki; Hozumi, Hideaki; Gao, Yongqian; Eda, Goki; Mattevi, Cecilia; Fujita, Takeshi; Yoshigoe, Akitaka; Ishizuka, Shinji; Adamska, Lyudmyla; Yamada, Takatoshi; et al.
Abstract : We report valence‐band electronic structure evolution of graphene oxide (GO) upon its thermal reduction. The degree of oxygen functionalization was controlled by annealing temperature, and an electronic structure evolution was monitored using real‐time ultraviolet photoelectron spectroscopy. We observed a drastic increase in the density of states around the Fermi level upon thermal annealing at ∼600 °C. The result indicates that while there is an apparent bandgap for GO prior to a thermal reduction, the gap closes after an annealing around that temperature. This trend of bandgap closure was correlated with the electrical, chemical, and structural properties to determine a set of GO material properties that is optimal for optoelectronics. The results revealed that annealing at a temperature of ∼500 °C leads to the desired properties, demonstrated by a uniform and an order of magnitude enhanced photocurrent map of an individual GO sheet compared to an as‐synthesized counterpart.